2021
DOI: 10.34288/jri.v3i3.233
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Readiness Attitude Toward Using Mobile Payment Systems Through Technology Acceptance Model

Abstract: The development of mobile payments is in line with the increasing number of application developers making features that are easy to use. The readiness of users to use mobile payments in making transactions is the main thing, whether users trust the applications used in transactions. This study attempts to model a framework where the technology readiness index and the technology acceptance model are used. Respondents in the study were in Jakarta with a purposive sampling technique, amounting to 204. Data proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Later, the questions in the scale were developed, their numbers increased and detailed and the TRI2 scale was published in 2015 [29]. TRI basically consists of four main factors: optimism, innovativeness, discomfort, and insecurity [30,31]. It has been researched and found in many studies that these factors affect individuals' attitudes towards technology and their readiness to adopt new technologies.…”
Section: Technological Readiness Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the questions in the scale were developed, their numbers increased and detailed and the TRI2 scale was published in 2015 [29]. TRI basically consists of four main factors: optimism, innovativeness, discomfort, and insecurity [30,31]. It has been researched and found in many studies that these factors affect individuals' attitudes towards technology and their readiness to adopt new technologies.…”
Section: Technological Readiness Indexmentioning
confidence: 99%
“…A study was conducted by Moxley and Czaja (2022) [38] on older adults' decisions regarding the adoption of technology, and it was revealed that the optimism dimension in the technology readiness scale positively affects attitudes towards the adoption of technology. Similarly, Sani et al (2021) [30] investigated technology readiness attitudes towards using mobile payment systems. In this study, they used the Technology Acceptance Model (TAM) and found that optimism, along with other factors, significantly affects the intention to use mobile payment systems.…”
Section: The Effect Of Optimism On Attitude Towards Usagementioning
confidence: 99%
“…Setidaknya terdapat tiga instrumen pembayaran non tunai, antara lain: paper-based: cek-bilyet giro dan nota debet, card-based: kartu kredit-kartu debet dan kartu ATM, electronic-based: e-commerce, e-money, internet banking dan mobile banking. Perkembangan menuju less cash society merupakan tren yang tidak dapat dihindari, perubahan tersebut antara lain didukung oleh perkembangan infrastruktur dan teknologi sistem pembayaran misalnya seperti kartu 'chip' (Arafat et al, 2020;Sani, Pusparini, Budiyantara, & Supit, 2023). PT.Swadharma Sarana Informatika untuk menghandel permasalahan jaringan pada data center milik Link Aja atau PT Fintek Karya Nusantara.…”
unclassified